A Confirmation Factor Analysis of the Potential Level Scale for Halal Tourist Sites in Lower Songkhla Lake - Suksanchananun, Waraporn; Juicharoen, Nhatphaphat; Wangthong, Suradetch (Ridwan Institute, 2023)
This research aims to examine the coherence between the potential levels of halal tourist attractions in the lower Songkhla lagoon area for Muslim tourists with empirical data. The sample consisted of 400 Muslim tourists. This research used questionnaire to collect the data which had a confidence value of Cronbach's Coefficient Alpha with a confidence value of 0.960. The researchers analyzed the structural validity of the potential levels about halal tourist attractions around the lower Songkhla lagoon for Muslim tourists by analyzing the second corroborative component using a statistical computer program. The second corroborative component analysis revealed that the potential levels of Halal Tourist Sites in the Lower Songkhla lagoon consisted of 6 components of equal importance with component weights of 0.78, 0.84, 0.83, 0.93, 0.90, and 0.87. The results of checking the consistency of the empirical component model found that the chi-square statistic is 391.24 at 259 degrees of freedom, the probability is 0.00, the relative chi-square statistic is 1.51, the Goodness of Fit Index (GFI) is 0.93 and the Adjusted Goodness of Fit Index (AGFI) is 0.90, the Comparative Fit Index (CFI) is 0.99, the Root Mean Square Residual (RMR) is 0.02 and the Root Mean Square Error of Approximation: RMSEA) is 0.04, which indicates that the potential levels of halal tourist attractions in the lower Songkhla lagoon area for Muslim tourists consistent with the empirical data and it consists of 6 components: Accessibility, Environment, Tourism Management, Facilities, Value, and Response.